Toxic truths Environmental justice and citizen science in a post-truth age - Davies, Thom; Mah, Alice (Manchester University Press, 2020)
This book examines the relationship between environmental justice and citizen science, focusing on enduring issues and new challenges in a post-truth age. Debates over science, facts, and values have always been pivotal within environmental justice struggles. For decades, environmental justice activists have campaigned against the misuses of science, while at the same time engaging in community-led citizen science. However, post-truth politics has threatened science itself. This book makes the case for the importance of science, knowledge, and data that are produced by and for ordinary people living with environmental risks and hazards. The international, interdisciplinary contributions range from grassroots environmental justice struggles in American hog country and contaminated indigenous communities, to local environmental controversies in Spain and China, to questions about "knowledge justice," citizenship, participation, and data in citizen science surrounding toxicity. The book features inspiring studies of community-based participatory environmental health and justice research; different ways of sensing, witnessing, and interpreting environmental injustice; political strategies for seeking environmental justice; and ways of expanding the concepts and forms of engagement of citizen science around the world. While the book will be of critical interest to specialists in social and environmental sciences, it will also be accessible to graduate and postgraduate audiences. More broadly, the book will appeal to members of the public interested in social justice issues, as well as community members who are thinking about participating in citizen science and activism. Toxic Truths includes distinguished contributing authors in the field of environmental justice, alongside cutting-edge research from emerging scholars and community activists.